The Effect of Work Environment on Job Satisfaction With Work Motivation as an Intervening Variable at Mulya Jaya Building Store Banyuasin - hakim, Malik; Veronica, Meilin; Yeni, Yeni (JEM17: Jurnal Ekonomi Manajemen, 2025)
This study aims to analyze the effect of the work environment on job satisfaction with work motivation as an intervening variable among employees of Toko Bangunan Mulya Jaya Banyuasin. The research problem is driven by the high employee turnover rate, which is influenced by low job satisfaction due to an unconducive work environment. This research applies a quantitative survey method. The population consists of 80 employees, all of whom were taken as samples using the total sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, simple regression analysis, t-test, R² test, and path analysis with SPSS version 29. The findings reveal that the work environment has a positive and significant effect on work motivation, work motivation has a positive and significant effect on job satisfaction, and the work environment has a positive and significant effect on job satisfaction through work motivation as an intervening variable. These results confirm that work motivation strengthens the relationship between the work environment and job satisfaction. The implication of this study highlights the importance of creating a supportive and comfortable work environment to enhance employee motivation and satisfaction, thereby reducing turnover and improving organizational productivity. Keywords: Job Satisfaction, Work Environment, Work Motivation.